GENETIC POLYMORPHISMS OF HLA-G GENE IN RHEUMATOID ARTHRITIS - Tabarek A. A.,; Reema M. A., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the influence of Human Leukocyte Antigens- G (HLA-G) gene polymorphisms on the risk of rheumatoid arthritis (RA). In the present study, blood samples were collected from 100 rheumatoid arthritis patients and 100 healthy controls. Serum levels of HLA-G in both patients and controls were measured using ELISA kit which was shown a higher significant differences (p< 0.05) in comparison between them (539.3 ng/ml and 139.3ng/ml) respectively.  The frequency of the allele and genotypes in the patient groups and control groups were determined using  Polymerase Chain Reaction (PCR) for 14 bp polymorhisms in exon 8 (rs66554220) while direct sequencing analysis was done to determine exon 2 (rs1130355) (G 1850 A) SNPs of human leucocyte antigens- G (HLA- G). There was statistically significant difference in all genotypes of HLA-G14-bp of exon 8 in RA patients in comparison with controls. The probability of homozygote genotype of insertion was (0.006), homozygote genotype of deletion was (0.003) and for heterozygote of insertion was (0.000) in comparison between RA patients and controls. From the results of odd ratio (OR) found that existence of homozygotes of insertion give protection effect from disease O.R= 0.44 while heterozygotes of deletion act as risk factor for disease O.R= 3.31. Homozygotes of deletion had no effect because was not found in patients groups. From the sequencing results of exon 2 of HLA-G gene found the mutation occur in position 1850 G>A which give three genotypes (GG, AG and AA). Calculations of genotypes frequency for exon 2 showed that GG and AA genotypes was associated with the disease with p- value (0.000) for both genotypes. While AG genotype showed no association with disease p value (0.449).From the results of odd ratio found that GG and AA of exon 2 gave protection effect from disease O.R( 0.29   and  0.76 ) respectively, while AG genotype acted as risk factor for disease O.R= 4.0.